Shear loaded friction-welded crosswise arranged timber boards. (January 2017) - Vallée, Till; Hahn, Benjamin; Weinand, Yves
Abstract: Friction welding of wood is a bonding technology that can be used for joining timber elements, and in which the adhesive is formed from thermally modified cell wall material within the substrate during the welding process. In this paper, this principle is used for manufacturing prototypes of friction welded crosswise arranged timber boards, structural element bearing similitude to cross-laminated timber (CLT) tested under in-plane shear loads. In addition to the experimental investigations, three different approaches of strength prediction were performed. Beside a simply analytical method, two different probabilistic principles based on the non-local Weibull theory of brittle failure were conducted.